Comment on “Cost-Effectiveness Analysis of Herpes Zoster Vaccination in 50- to 85-Year-Old Immunocompetent Belgian Cohorts: A Comparison between No Vaccination, the Adjuvanted Subunit Vaccine, and Live-Attenuated Vaccine” - Giannelos, Nikolaos; Nishimwe, Marie Libérée; Lecrenier, Nicolas (PharmacoEconomics, 2022)
While valuable in being the first publication examining the cost effectiveness of RZV using local Belgian data, the publication underestimates the public health benefits of RZV vaccination as well as its cost-effectiveness levels for Belgium, primarily because (a) it applies HZ incidence rates adjusted to immunocompetent individuals using a simplistic and biased calculation and (b) it applies the aforementioned adjustments to RZV versus no vaccination comparisons although RZV is indicated for both immunocompetent and immunocompromised individuals. [...]adjusting the overall incidence rates of HZ to account for immunocompetent subjects is unnecessary for RZV as the vaccine is indicated for the prevention of HZ in adults 18 years of age or older who are immunodeficient or immunosuppressed due to disease or therapy. Zostavax Summary of Product Characteristics (SmPC); 2022. https:// www.ema.europa.eu/ documents/ product- infor mation/zostavax-epar-product-information_en.pdf Authors' Reply to Comment on "Cost-Effectiveness Analysis of Herpes Zoster Vaccination in 50- to 85-Year-Old Immunocompetent Belgian Cohorts: A Comparison Between No Vaccination, the Adjuvanted Subunit Vaccine, and Live-Attenuated Vaccine" Accepted: 28 August 2022 / Published online: 26 September 2022 © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2022 Dear Editor, We thank Giannelos et al. [...]the authors object to the fact that, along with a head-to-head comparison between both vaccines (RZV and ZVL), we estimated the cost effectiveness of RZV versus no vaccination in immunocompetent people, using data pertaining to immunocompetent people.